Labour Migration, Policies and Skills Development - Pudasaini, Sangita (Political Science Journal, 2025)
The Nepal Labour Force Survey 2017-18 indicates that approximately half a million young individuals join the workforce in Nepal annually. Socio-economic factors, gender discrimination, the effects of climate change, and the limited availability of domestic employment opportunities contribute significantly to the growing trend of labor migration in search of better job prospects. However, many migrants encounter challenges in their destination countries due to a lack of relevant skills. This report seeks to examine and analyze the policy frameworks related to migration governance, the conditions of migrants, and the development of skills. The analysis is based on secondary data sources.